Type I collagen promotes the migration and myogenic differentiation of C2C12 myoblasts via the release of interleukin-6 mediated by FAK/NF-κB p65 activation. Issue 1 (4th December 2019) - Liu, Xiaoling; Gao, Yanfang; Long, Xinyu; Hayashi, Toshihiko; Mizuno, Kazunori; Hattori, Shunji; Fujisaki, Hitomi; Ogura, Takayuki; Wang, Dan Ohtan; Ikejima, Takashi
Abstract : Type I collagen has the potential to promote the migration and differentiation of C2 C12 myoblast via IL-6 release that was mediated by FAK/NF-κB pathway. Abstract : Skeletal muscle regeneration is a complicated process, requiring the proliferation, migration and differentiation of myoblasts whose processes are highly regulated by the extracellular matrix (ECM) surrounding the muscle tissues in vivo . However, the effects of respective ECM components on the regulation of myoblast behaviors are unknown. In this study, we report on the effect of collagen I, a major ECM component in muscle tissue and a popular food supplement, on mouse C2C12 myoblast proliferation, migration and differentiation as well as the underlying mechanisms. Collagen I (col 1) enhances the migration and myogenic differentiation of C2C12 cells, but has no effect on cell proliferation. Col I significantly promotes the production and release of interleukin-6 via nuclear translocation of nuclear factor κB (NF-κB) p65. The release of IL-6 plays a critical role in the col I-enhanced migration and differentiation of C2C12 cells. Furthermore, col I increases phosphorylation of focal adhesion kinase (FAK) that is involved in the nuclear translocation of NF-κB p65. Collectively, col I enhances the migration and differentiation of C2C12 cells through IL-6 release induced by FAK/NF-κB p65 activation.